THE EFFECT OF JOB BURNOUT AND ORGANIZATIONAL CLIMATE ON WORKPLACE INCIVILITY IN NURSES - Azmi Kusumastuti Utomo; Dewi Syarifah (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Job burnout is a syndrome of emotional exhaustion and cynicism that often occurs in workers in the field of community service. The organizational climate is a set of work quality that becomes the cause of job burnout. This is then able to trigger workplace incivility, which also occurs in nurses as workers in the field of community service.